PENGEMBANGAN POTENSI MASYARAKAT BANGUNMULYO MELALUI PROGRAM I-CREATEDI (INOVASI,KREATIF DAN MANDIRI) HOME INDUSTRI SALAK PONDOH - Dyah Pikanthi Diwanti; Andes Fuady Dharma (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2019)
This empowerment program aims to increase the productivity of the community, where there is still no public awareness of the importance of existing potential so that some strengths and opportunities hampered by good constraints Both inside and outside challenges. The method of implementation done by counselling, training and mentoring to the residents and partners namely PKK mothers to maximise the outcome of the series of activities, besides the leaflet as an educational facility given as a guide. From the implementation of Salak processing activities to brownies, there are some indications of the success of the program. Among them, the attitude of citizens who showed a positive change is the increase of awareness of the majority of farmers who are the most important creativity processed salak to be made independently and in groups, can be consumed and can be sold to Increase of citizen income. Keywords: Bangunmulyo, Salak, community productivity